Comparative accuracy assessment of global DTM and DTM generated from Soviet topographic maps for the purposes of road planning. Issue 4 (2nd October 2017) - Hutsul, Taras; Smirnov, Yaroslav
Abstract: This article analyses the accuracy of global DTM comparatively to the Soviet topographic maps. The main aim of this study is to estimate the possibility of utilising global DTM for the purposes of road planning. In order to reach this aim, three separate territories with mountain, hill and plain topography were chosen. A DEM was generated for those territories from three different scale levels of Soviet topographic maps. The generated DEM rasters where then subtracted from SRTM and ASTER GDEM global DTMs. Results of the subtraction were analysed using statistical methods and verified with ground data. The Possibility of the replacement of DTMs generated from topographic maps by the global DTM data was proven for the different territories. The results obtained could be useful for the road engineers who still use Soviet topographic maps for the purposes of road planning. Also, some of the findings might be interesting for GIS-professionals who frequently use global DTMs.